EPIDEMIOLOGY AND THERAPEUTIC STUDIES ON NEMATODES INFECTION IN CATTLE AT DISTRICT QILLA ABDULLAH, BALOCHISTAN - M. Ramzan; N. Ahmad; K. Ashraf; K. Saeed; A. `Z. Durrani; S. Jan; Rafiuddin; M. A. Khan (Journal of Animal and Plant Sciences, 2017)
A study was conducted to assess the epidemiological and therapeutic control aspects of gastrointestinal nematodes of cattle at district Qilla Abdullah, Balochistan, from March 2012 to February 2013.A total of 600 fecal samples (50 samples per month) were examined during the study period. Fecal analysis showed overall higher nematodes prevalence as 27.99%. Among nematodes higher prevalence was recorded with infection of Ostertagia in cattle. Among age groups, cattle of <1 year of age presented higher nematodes prevalence than 1-2 years and >2 years age groups. Female cattle were infected higher than male animals with nematode parasites. The nematodes were prevalent throughout the year, however a peak infection was recorded during August and September. The therapeutic studies showed higher (89-100%) reduction of EPG in cattle calves treated with Ivermectin followed by Levamisole (88-100%) and Oxfendazole (86-100%).The present study was accomplished for a better understanding of gastrointestinal nematode infections under local climate and management system of the study area of Balochistan.
Keywords: Gastrointestinal Nematodes; Cattle; Hemonchus; Ostertagia; Trichostrongylus; Nematodirus; Trichuris; Qilla Abdullah